Transcriptome Profiling of Pacu (Piaractus mesopotamicus) Challenged With Pathogenic Aeromonas hydrophila: Inference on Immune Gene Response - Mastrochirico-Filho, Vito Antonio; Hata, Milene Elissa; Kuradomi, Rafael Yutaka; de Freitas, Milena Vieira; Ariede, Raquel Belini; Pinheiro, Daniel Guariz; Robledo, Diego; Houston, Ross; Hashimoto, Diogo Teruo (Frontiers in Genetics, 2020)
Pacu (Piaractus mesopotamicus) is a Neotropical fish of major importance for South American aquaculture. Septicemia caused by Aeromonas hydrophila bacteria is currently considered a substantial threat for pacu aquaculture that have provoked infectious disease outbreaks with high economic losses. The understanding of molecular aspects on progress of A. hydrophila infection and pacu immune response is scarce, which have limited the development of genomic selection for resistance to this infection. The present study aimed to generate information on transcriptome of pacu in face of A. hydrophila infection, and compare the transcriptomic responses between two groups of time-series belonging to a disease resistance challenge, high mortality (HM) and mortality plateau (PM) groups of individuals. Nine RNA sequencing (RNA-Seq) libraries were prepared from liver tissue of challenged individuals, generating ~160 million 150 bp pair-end reads. After quality trimming/cleanup, these reads were assembled de novo generating 211,259 contigs. When the expression of genes from individuals of HM group were compared to individuals from control group, a total of 4,413 differentially expressed transcripts were found (2,000 upregulated and 2,413 downregulated candidate genes). Additionally, 433 transcripts were differentially expressed when individuals from MP group were compared with those in the control group (155 upregulated and 278 downregulated candidate genes). The resulting differentially expressed transcripts were clustered into the following functional categories: cytokines and signaling, epithelial protection, antigen processing and presentation, apoptosis, phagocytosis, complement system cascades and pattern recognition receptors. The proposed results revealing relevant differential gene expression on HM and PM groups which will contribute to a better understanding of the molecular defense mechanisms during A. hydrophila infection.